Interaction of silver nanoparticles with Escherichia coli and their cell envelope biomolecules. (11th September 2013) - Ansari, Mohammad Azam; Khan, Haris Manzoor; Khan, Aijaz Ahmed; Ahmad, Mohammad Kaleem; Mahdi, Abbas Ali; Pal, Ruchita; Cameotra, Swaranjit Singh
<x xml:space="preserve">Abstract</x> The antibacterial effect of AgNPs was investigated by determining MIC/MBC and growth kinetics assay. The lowest MIC/MBC was found to be in the range of 11.25–22.5 µg ml−1. The growth kinetics curve shows that 25 µg ml−1 AgNPs strongly inhibits the bacterial growth. Confocal laser scanning electron microscopy (CLSM) shows that as the concentration of NPs increases, reduction in the number of cells was observed and at 50 µg ml−1 of NPs, 100% death was noticed. Scanning electron microscopy (SEM) shows cells were severely damaged with pits, multiple depressions, and indentation on cell surface and original rod shape has swollen into bigger size. High resolution‐transmission electron microscopic (HR‐TEM) micrograph shows that cells were severely ruptured. The damaged cells showed either localized or complete separation of the cell membrane. The NPs that anchor onto cell surface and penetrating the cells may cause membrane damage, which could result in cell lysis. The interaction of AgNPs to membrane biomolecules; lipopolysaccharide (LPS) and L‐α‐phosphatidyl‐ethanolamine (PE) were investigated by attenuated total reflectance–fourier transform infrared (ATR–FTIR) spectroscopy. LPS and PE showed IR spectral changes after AgNPs exposure. The O‐antigen part of LPS was responsible for interaction of NPs through hydrogen bonding. The phosphodiester bond of PE was broken by AgNPs, forming phosphate monoesters and resulting in the highly disordered alkyl chain. The AgNPs‐induced structural changes in phospholipid may lead to the loss of amphiphilic properties, destruction of the membrane and cell leaking. The biomolecular changes in bacterial cell envelope revealed by ATR–FTIR provide a deeper understanding of cytotoxicity of AgNPs.